Budd-Chiari Syndrome Imaging Diagnosis: State of the Art and Future Perspectives - Giorgia Porrello; Giuseppe Mamone; Roberto Miraglia (Diagnostics, 2023)
Budd-Chiari syndrome (BCS) is a rare hepatic vascular disorder defined by the presence of partial or complete impairment of hepatic venous drainage in the absence of right heart failure or constrictive pericarditis. Several conditions can lead to BCS, from hypercoagulable states to malignancies. Primary BCS is the most common subtype, and usually bartends hypercoagulability states, while secondary BCS involves tumor invasion or extrinsic compression. A combination of clinical and imaging features leads to the diagnosis of BCS, including (1) direct signs: occlusion or compression of the hepatic veins and/or inferior vena cava, and the presence of venous collaterals; (2) indirect signs: morphological hepatic changes with caudate lobe enlargement; inhomogeneous enhancement, and hypervascular nodules. From a clinicopathological point of view, two forms of BCS can be distinguished: acute and subacute/chronic BCS, although asymptomatic and fulminant forms are also possible. Acute presentations are rare, and symptoms include hepatomegaly, ascites, and hepatic insufficiency. Subacute/chronic forms are the most common presentation, with dysmorphic liver and variable degrees of fibrosis deposition. Patients with chronic BCS can develop benign regenerative nodules (large regenerative nodules or FNH [Focal Nodular Hyperplasia]-like lesions), but are also at a higher risk of hepatocellular carcinoma (HCC). The radiologist role is therefore fundamental in both diagnosis and surveillance of BCS. The aim of this review is to present all clinical and imaging signs that can help to reach the diagnosis of BCS, with their clinical significance, providing tips and tricks for the cross-sectional diagnosis of this condition.